2009
DOI: 10.1002/hep.22800
|View full text |Cite
|
Sign up to set email alerts
|

The genes that underlie fatty liver disease: The harvest has begun

Abstract: Fallon PG, Richardson EJ, McKenzie GJ, McKenzie AN. Schistosomeinfection of transgenic mice defines distinct and contrasting pathogenic roles for IL-4 and IL-13: IL-13 is a profibrotic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…A previous study identified that Asians and Hispanics showed a higher degree of steatosis than Whites and other ethnicities [ 20 ]. The prevalence and histological features of NAFLD also have obvious ethnic difference [ 21 , 22 ]. It was well documented that the association between NAFLD and enhanced inflammation only remained significant in white people but not Chinese, African American and Hispanic people after multivariable adjustment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified that Asians and Hispanics showed a higher degree of steatosis than Whites and other ethnicities [ 20 ]. The prevalence and histological features of NAFLD also have obvious ethnic difference [ 21 , 22 ]. It was well documented that the association between NAFLD and enhanced inflammation only remained significant in white people but not Chinese, African American and Hispanic people after multivariable adjustment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Romeo and colleagues 80 recently reported that homozygotes for a particular PNPLA3 polymorphism were more likely to have steatosis and evidence of cell injury. 81 Moreover, the allele was more common among Hispanic Americans compared with African Americans, indicating that this allele may be a major determinant of ethnic variation. Although its role relative to other genetic variables remains to be established, genetic variation in PNPLA3 may prove to be a significant predictor of severe steatosis under conditions of calorie excess.…”
Section: Familial Associations Genetics and Ethnicity In Nafldmentioning
confidence: 98%
“…Although on the horizon, genomewide association studies of defined liver phenotypes are still limited. 34 Therefore, hypothesisfree genetic research has taken advantage of wellcharacterized animal models and large intercrosses of inbred mice to unravel yet unknown genes with a direct impact on liver injury and fibrosis. 35 By this approach, different risk loci for liver fibrosis have been detected.…”
Section: Genetic Evidence For a Role Of Chemokines In Liver Inflammatmentioning
confidence: 99%